Evaluation of Human Spermatozoa Mitochondrial Membrane Potential Using the JC‐1 Dye. Issue 9 (6th September 2022) - Carrageta, David F.; Freire‐Brito, Laís; Oliveira, Pedro F.; Alves, Marco G.
Abstract: Mitochondria are fundamental for human spermatozoa motility and fertilizing ability. Mitochondria participate not only in ATP production, but also in reactive oxygen species production, redox equilibrium, and calcium regulation, all of which are central for human spermatozoa motility, capacitation, acrosome reaction, and ultimately, oocyte fertilization. Mitochondrial membrane potential is a key indicator of mitochondrial health and activity. Most commonly used methods for the study of mitochondrial membrane potential, however, cannot be applied to human spermatozoa due to their unique characteristics, including high motility and time‐dependent decay of quality, limiting the study of this important parameter in these cells. Here, we describe an easy, fast, and cheap protocol for the quantitative evaluation of human spermatozoa mitochondrial membrane potential, using the fluorescent cationic dye 5, 5, 6, 6′‐tetrachloro‐1, 1′, 3, 3′‐tetraethylbenzimi‐dazoylcarbocyanine iodide (JC‐1). JC‐1 is a sensitive marker for mitochondrial membrane potential, exhibiting a potential‐dependent accumulation in the mitochondria. At high mitochondrial membrane potential, JC‐1 forms J‐aggregates, which emit red fluorescence, whereas at low mitochondrial membrane potential, JC‐1 remains at its monomer state, which emits green fluorescence. We first describe how to evaluate human spermatozoa mitochondrial membrane potential using JC‐1 and a fluorescence plate reader, for high‐throughput studies. The calculation of the JC‐1 ratio (indicative of the J‐aggregates/monomers ratio) is then used to quantitatively evaluate mitochondrial health and activity. In addition, we describe an imaging protocol for the qualitative evaluation of human spermatozoa mitochondrial membrane potential using a fluorescence microscope. This allows for a visual analysis of the results that can complement the quantitative data. These protocols can be used to study the effects of spermatozoa exposure to compounds of interest, and alterations due to diseases or different conditions. While these protocols are illustrated with human spermatozoa, they can be adapted and used on spermatozoa of different species. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Quantitative evaluation of human spermatozoa mitochondrial membrane potential using the JC‐1 dye and a fluorescence plate reader Basic Protocol 2 : Qualitative evaluation of human spermatozoa mitochondrial membrane potential using the JC‐1 dye and fluorescence microscopy Support Protocol : Preparation of the JC‐1 working solution